Interplay between Myokine Profile and Glycemic Control in Type 2 Diabetes Mellitus Patients with Heart Failure - Berezin, A. A.; Obradovic, Z.; Novikov, E. V.; Boxhammer, E.; Lichtenauer, M.; Berezin, A. E.; Новіков, Євген Вячеславович; Березін, Олександр Євгенійович (My University, 2022)
Abstract: Type 2 diabetes mellitus (T2DM) remains a powerful predictor of progressive heart failure (HF), but it is not clear whether altered glycemic control interferes with HF progression via an impaired profile of circulating myokines. The aim was to investigate plausible effects of glucose control on a myokine signature in T2DM patients affected by chronic HF. We selected 372 T2DM patients from the local database and finally included 314 individuals suffering from chronic HF and subdivided them into two groups according to glycosylated hemoglobin (HbA1c) levels (<6.9% and 7.0%). Echocardiography and Doppler examinations along with biomarker measurements were performed at the baseline of the study. The results showed that irisin levels were significantly lower in patients with HbA1c 7.0% than in those with HbAc1 < 6.9%, whereas concentrations of apelin, myostatin and adropin did not significantly differ between these two groups. We also identified numerous predictors of poor glycemic control, but only N-terminal brain natriuretic propeptide (odds ratio [OR] = 1.07; 95% confidence interval [CI] = 1.02–1.10, p = 0.04) and irisin (OR = 1.09; 95% CI = 1.04–1.17, p = 0.001) remained independent predictors of the dependent variable. In conclusion, we found that decreased levels of irisin were associated with poor glycemic control in T2DM patients with HF regardless of clinical conditions and other biomarkers.
Berezin A. - https://orcid.org/0000-0002-0446-3999
Keywords: type 2 diabetes mellitus; heart failure; myokines; irisin; apelin; myostatin; adropin; biomarkers; prediction